Cohort profile: Mental Health Living Longer: a population-wide data linkage to understand and reduce premature mortality in mental health service users in New South Wales, Australia. Issue 11 (19th November 2019) - Sara, Grant; Arumuganathan, Myu; Chen, Wendy; Wu, Fred; Currow, David; Large, Matthew; Mulder, Cornelis; Ramanuj, Parashar Pravin; Burgess, Philip M
Abstract : Purpose: Health systems must move from recognition to action if we are to address premature mortality in people with mental illness. Population data registers are an essential tool for planning and monitoring improvement efforts. The Mental Health Living Longer (MHLL) programme establishes a population-wide data linkage to support research translation and service reform in New South Wales (NSW), Australia. Participants: A total of 8.6 million people who have had contact with NSW public and private health services between July 2001 and June 2018 are currently included in the study. Data include more than 120 million linked records from NSW data collections covering public and private hospital care, emergency departments, ambulance, community mental health services, cancer notifications and care, and death registrations. Linkage is occurring with population-wide breast and cervical cancer screening programmes. Data will be updated 6 monthly. Findings to date: The cohort includes 970 145 people who have received mental healthcare: 79% have received community mental healthcare, 35% a general hospital admission with a primary mental health diagnosis and 25% have received specialist mental health inpatient care. The most frequent pattern of care is receipt of community mental healthcare only (50%). The median age of the mental health cohort is 34 years, and three-quarters are younger than 53 years. Eleven per cent of the mental health cohort had died during the observation period. Their median age at death was 69 years, which was younger than the median age at death for people accessing other health services. Future plans: The MHLL programme will examine (i) all-cause mortality, (ii) suicide, (iii) cancer mortality and (iv) medical mortality. Within each theme, the programme will quantify the problem in mental health service users compared with the NSW population, describe the people most affected, describe the care received, identify predictors of premature mortality, and identify variation and opportunities for change.